2018
DOI: 10.1111/2041-210x.13065
|View full text |Cite
|
Sign up to set email alerts
|

Parameterizing the robust design in the BUGS language: Lifetime carry‐over effects of environmental conditions during growth on a long‐lived bird

Abstract: Since the initial development of the robust design, this capture‐recapture model structure has been modified to estimate temporary emigration and expanded to include auxiliary information such as band recovery and live resight data using maximum likelihood approaches. These developments have allowed investigators to separately assess individual and group effects on true survival, site fidelity, and temporary emigration. Additionally, recent advances in the BUGS language have allowed researchers to develop incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…As predicted, and indicated by previous research (Leach et al, ), we observed positive correlations between adult and juvenile survival. Brent family groups remain together from hatch through late spring (Sedinger, Nicolai, Lensink, Wentworth, & Conant, ), where we would expect environmental variation which impacts adult survival to affect juvenile survival as well, despite strong carry‐over effects of environmental conditions during growth on first‐year survival, and lifetime fitness, of juvenile brent (Riecke et al, ; Sedinger et al, , ). Long‐term declines in both adult (Leach et al, ; Riecke et al, ) and juvenile survival (Leach et al, ) have critical implications for brent populations, which are also experiencing declines in fecundity (Ward, Amundson, Stehn, & Dau, ) and population size (Sedinger, Riecke, Leach, & Ward, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted, and indicated by previous research (Leach et al, ), we observed positive correlations between adult and juvenile survival. Brent family groups remain together from hatch through late spring (Sedinger, Nicolai, Lensink, Wentworth, & Conant, ), where we would expect environmental variation which impacts adult survival to affect juvenile survival as well, despite strong carry‐over effects of environmental conditions during growth on first‐year survival, and lifetime fitness, of juvenile brent (Riecke et al, ; Sedinger et al, , ). Long‐term declines in both adult (Leach et al, ; Riecke et al, ) and juvenile survival (Leach et al, ) have critical implications for brent populations, which are also experiencing declines in fecundity (Ward, Amundson, Stehn, & Dau, ) and population size (Sedinger, Riecke, Leach, & Ward, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists have both highlighted (Arnold et al, ; Péron, ; Servanty et al, ) and debated (Arnold, Afton, Anteau, Koons, & Nicolai, ; Lindberg, Boomer, Schmutz, & Walker, ) the utility of these approaches. Capture–recapture (Riecke, Leach, Gibson, & Sedinger, ) and integrated population models can also be used to examine covariation among parameters such as survival and breeding propensity. This allows researchers to examine life‐history trade‐offs at the individual or population level (Cam et al, ), as well as correlations among other demographic parameters (Kindsvater et al, ; Koons, Arnold, & Schaub, ; Link & Barker, ; Schaub, Jakober, & Stauber, ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are likely due, in part, to discrepancies between MAPS and BBS data sets, which differ in sizes and spatio‐temporal distribution of sampling units. Thus, ecological interpretation of the recruitment component of our model must be tempered due to inclusion of error associated with discrepancies in the sampling processes between data sets (Riecke, Leach, Gibson, & Sedinger, ). Alternative models for the capture‐recapture data, such as Jolly Seber (JS) models (Link & Barker, ; Royle & Dorazio, ) could be incorporated to inform recruitment directly.…”
Section: Discussionmentioning
confidence: 99%
“…A Bayesian robust design model (Nichols & Pollock, 1990; Pollock, 1982) was used to estimate abundance, survival, and site fidelity while accounting for imperfect detection using code based on Riecke et al. (2018). Specifically, detection probability ( p t ) was estimated as the probability an individual available for detection during time t was in fact detected during at least one secondary occasion, abundance ( N t ) was estimated as the number of individuals in the study area during each primary period, survival ( ϕ t ) was estimated as the probability an individual in the population at time t survived to time t + 1 and did not permanently emigrate from the study area, and site fidelity (γ t ) was estimated as the probability an individual alive and in the area at time t remained in the area at time t + 1 and was available for detection.…”
Section: Methodsmentioning
confidence: 99%